The Use of Strong Language in Peaky Blinders Television Series: A Gender Study - Rizky Femilya Elsa (Universitas Muhammadiyah Semarang, 2023)
Swearing has become a prevalent aspect of language use in modern society, but it remains taboo for some individuals, particularly women who are expected to conform to traditional gender roles. Men are often perceived as normal when using strong language, while women may face negative reactions for doing so, because in a way that does not apply to males, women who swear may face unfavorable moral as well as negative social judgments. The total of strong language found on Peaky Blinders season 4 episode 1 are 42 sentences which 83,3% of it dominated by men and 16,7% are spoken by women. By employing a qualitative approach, it resulted a conclusion that most swear word dominated by men. Furthermore, the study categorized each sentence into McEnery's (2005) fifteen distinct linguistic forms of swearing, facilitating a comprehensive analysis of the findings based on relevant theoretical frameworks. Understanding the intricacies of strong language use can contribute to a more comprehensive understanding of language and gender dynamics